Development of moving object catcher robot using sbc - Lim, Zhi Shun (School Of Computer And Communication Engineering, University Malaysia Perlis, 2015)
Automated video analysis is important for many vision applications such as surveillance, traffic supervision, people tracking, augmented reality, vehicle navigation, etc. There are many existing products that capable of detect and tracking a moving object. However, some of the products that only capable of tracking moving based on colour. Tracking using colour only perform well when the colour of target is unique compared to its background. Besides, most of the system proposed only able to detect and track moving objects but cannot perform a reaction on the tracked object. This project presents an idea to develop a moving object catcher robot using SBC. To detect moving object, background subtraction has been used in this project. The catcher robot is built with a DC motor and a motor driver model L293D. The result shows that background objects are filtered and moving object detected is being highlighted and tracked. Any moving object has been detected is considered based on its coordination on the camera to decide the location of it. The catcher robot react based on the location and moving direction of the object detected.